Percepções de mulheres em situação de violência na UFPB - Silva, Bruna Chaves Steinbach (2021)
The research has as its object of analysis the perceptions of women in situations of violence at the Federal University of Paraíba: To this end, we sought to analyze the socioeconomic profile of the victims, the consequences of violence in the learning process, types of violence identified in the UFPB and which the reception structure of these women. The research also provided a description of the functioning and dynamics of the Policy Committee for the Prevention and Confrontation of Violence Against Women - COMU - in the sense of welcoming women in situations of violence at UFPB. As extra data we present information to the impact of the pandemic on gender violence in Brazil. The chosen research field was the Federal University of Paraíba, which, despite being a space for discussions, has shown through the groups and movements active on the campus the reproduction of different types of violence against women and gender. The research had a mixed methodology, in addition to semi structured interviews, online observation of the field was carried out through the work of women's groups, the bibliographical survey with authors who focused on feminist studies and violence against women, until we arrived data and types of violence in universities in Brazil and finally on the campus of the Federal University of Paraíba. It was found that the experience of this phenomenon in the lives of these women compromises their full intellectual development, their emotional and financial autonomy as they endure for years as victims of violence, living with the aggressor and taking a long time to realize that it is necessary to seek help and host to get out of this situation. However, educational institutions do little to prevent the problem, as the omission and silence reveal the lack of effective public actions and policies to fight violence, as these women need care and protection.